Relative prosthesis‐patient mismatch after transcatheter aortic valve replacement: The impact of morbid obesity. Issue 2 (27th August 2016) - Airhart, Sophia; Medvedev, Ivan; Dean, Larry S.
Abstract : Prosthesis‐patient mismatch (PPM) is defined as a small effective orifice area (EOA) of a normally functioning prosthetic valve in relation to patient body size. Even moderate impediment to forward flow has been associated with an increase in all‐cause mortality. We report an unusual cause of PPM where a transcatheter implantation of a large EOA valve in an aortic position results in relative PPM in a patient with morbid obesity. © 2016 Wiley Periodicals, Inc.